Dihydroartemisinin attenuates PM-induced lung injury by inhibiting inflammation and regulating autophagy - Liu, Lingjing; Li, Jingli; Xue, Yincong; Xie, Shuying; Dong, Nian; Chen, Chengshui (Frontiers in Public Health, 2025)
ObjectiveThe study investigates the effects and mechanisms of dihydroartemisinin (DHA) in mitigating lung injury induced by particulate matter (PM).MethodsThe lung injury model was induced by PM particles in vivo and in vitro. Hematoxylin and Eosin (H&E) staining was utilized for the detection of the thickening of airway wall and the infiltration of inflammatory cells in mouse lung tissue. The expressions of inflammatory factors were detected in alveolar lavage fluid and cell supernatant. TUNEL (Terminal deoxynucleotidyl transferase dUTP nick end labeling) staining, Caspase-1, Bcl-2-associated X protein (Bax), B-cell lymphoma 2 (Bcl-2), microtubule-associated protein 1 light chain 3-II (LC3-II) and Belcin-1 were used to observe the apoptosis and autophagy related expressions in mouse lung tissue, and p-p65 was detected by immunofluorescence.ResultsH&E staining revealed DHA alleviates PM-induced lung injury in vivo. Moreover, DHA reduced IL-6, IL-8, and IL-1β levels by ~50% (p < 0.05), highlighting its anti-inflammatory effects. Furthermore, immunohistochemistry showed that DHA treatment inhibited the pro-apoptotic expression of Bax/BCL2 and cleaved-Caspase-3, respectively. In addition, immunofluorescence staining revealed that the LC3-II and Beclin-1 levels dramatically increased in the PM group compared to Control group, but greatly reduced by DHA. Further, we found that DHA inhibited the activation of the NF-KB signaling pathway.ConclusionDHA protects against PM-induced lung injury through anti-inflammatory, anti-apoptotic, and autophagy-regulating mechanisms, offering a potential drug option for improving PM-induced lung injury.